LINGUISTIC FEATURES OF DIPLOMATIC CORRESPONDENCE (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract Diplomatic correspondence, as a specialized form of communication in international relations, embodies unique linguistic features essential for fostering effective dialogue and negotiation between nations. This paper explores the foundational elements of diplomatic language, emphasizing its formal, precise, and culturally sensitive nature. Diplomats employ language strategically to maintain politeness, avoid confrontation, and navigate sensitive topics using euphemisms and diplomatic language. Structured formats and adherence to protocol underscore the professionalism and clarity necessary in diplomatic exchanges.